2009
DOI: 10.1089/jmf.2008.0242
|View full text |Cite
|
Sign up to set email alerts
|

In VitroBile Acid Binding and Short-Chain Fatty Acid Profile of Flax Fiber and Ethanol Co-Products

Abstract: Fibers from flaxseed and co-products from ethanol production could be potential sources of dietary fiber in human diet. In vitro fermentation and bile acid binding models were used to investigate the metabolic effects of lignaMax (Bioriginal Food and Science Corp., Saskatoon, SK, Canada) flax meal, spent flax meal, soluble flax gum, wheat insoluble fiber (WIF), and rye insoluble fiber (RIF). Wheat and rye bran were used as reference samples. Bile acid binding of substrates was analysed at taurocholate ([(14)C]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…These results demonstrated the potential ability of pure mucilage as well as crude flaxseed mucilage in kefir systems with or without probiotics to enhance the microbial survival and growth.The polysaccharides of flaxseed mucilage have been classified in two groups of neutral and acidic fraction which mainly composed of arabinoxylan and rhamonogalacturonan I, respectively (Naran, Chen, & Carpita, 2008;Warrand et al, 2003). Our findings confirm the results reported by (Fodje et al, 2009) which showed the highest fermentation rate of flaxseed mucilage in comparison to wheat or rye bran, due to higher soluble fibre content in flaxseed mucilage. Kefir samples without probiotics and supplemented with probiotic 1 showed a significantly (P < 0.001) higher bacteria growth in the samples containing pure flaxseed mucilage than crude flaxseed mucilage (Figure 3 flaxseed mucilage while the same trend was not observed for Bifidobacterium lactisor combined probiotics treatments (Figure 3(c) and (d)).…”
Section: Microbial Analysessupporting
confidence: 93%
See 2 more Smart Citations
“…These results demonstrated the potential ability of pure mucilage as well as crude flaxseed mucilage in kefir systems with or without probiotics to enhance the microbial survival and growth.The polysaccharides of flaxseed mucilage have been classified in two groups of neutral and acidic fraction which mainly composed of arabinoxylan and rhamonogalacturonan I, respectively (Naran, Chen, & Carpita, 2008;Warrand et al, 2003). Our findings confirm the results reported by (Fodje et al, 2009) which showed the highest fermentation rate of flaxseed mucilage in comparison to wheat or rye bran, due to higher soluble fibre content in flaxseed mucilage. Kefir samples without probiotics and supplemented with probiotic 1 showed a significantly (P < 0.001) higher bacteria growth in the samples containing pure flaxseed mucilage than crude flaxseed mucilage (Figure 3 flaxseed mucilage while the same trend was not observed for Bifidobacterium lactisor combined probiotics treatments (Figure 3(c) and (d)).…”
Section: Microbial Analysessupporting
confidence: 93%
“…The heterogenic polysaccharide, flaxseed mucilage/gum, is the soluble fiber components that constitute about 6 to 8% of the whole seed (on a dry weight basis; Cui & Mazza, 1996). Fodje, Chang, and Leterme (2009) demonstrated that high amounts of acetate and propionate (short-chain fatty acids) resulted when flaxseed was fermented in vitro. Generally, fermentation rate was highest in soluble flaxseed gum relative to flax meal orwheat and rye bran, owing to its high solubility, thus, flaxseed mucilage could be a source of dietary fibre (Fodje et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When flaxseed was fermented in vitro, it was resulted in producing the high amounts of acetate and propionate (short-chain fatty acids, SCFA) (Fodje et al, 2009). Also, when flaxseed mucilage used as food additives, it could capture free radicals to have anti-tumor and antioxidant properties and could oxidize proteins, lipid or DNA to prevent cancers, simultaneously (Gutiérrez et al, 2010).…”
Section: Fig 2 Various Beneficent Effects Of Dietary Lignan In Flaxmentioning
confidence: 99%
“…As well as clear sour taste with increased levels of linseed oil initial 1.5% (T3), also whey weeping increase in yoghurt supplemented with linseed oil. Fodje et al (2009) mentioned that high amounts of acetate and propionate (short-chain fatty acids) resulted when flaxseed oil was fermented in vitro. Total scores showing high acceptability towards the flavour, consistency and appearance of yoghourt supplementation with linseed oil in both T1 and T2 treatments which were almost equally preferred compared to the control sample.…”
Section: Rheological Properties: Syneresis Valuementioning
confidence: 99%